Building a health communication brand for University of Texas System tobacco control. Issue 4 (19th May 2019) - Mackert, Michael; Case, Kathleen; Lazard, Allison; Oh, Jeeyun; Hughes Wagner, Jessica; Hawk, Ernest; Cofer, Jennifer; Hurst, Alex; Elerian, Nagla; Lakey, David
Abstract: Objective: Despite declining cigarette smoking rates in the US, there is a continued need for tobacco prevention education campaigns to reach young adults. Recognizing the need for improved tobacco control messaging, the University of Texas (UT) System engaged The University of Texas at Austin Center for Health Communication to develop a brand and message that would strengthen tobacco control efforts at its 14 institutions.Methods: This article describes the iterative process involved in creating a brand for tobacco control, including an environmental scan, identifying potential message themes, and creating and refining logos.Results: This article highlights the process of developing a system-wide tobacco control brand. Specifically, the process included coordinating an interdisciplinary team with content and design experts, and presenting ideas to stakeholders for serial feedback and refinement, among others.Conclusions: Ultimately, this project offers a model for other systems of higher education interested in pursuing similar initiatives.